Nasal neuroglial heterotropia: a rare mimicker of dermoid cyst: a case report - D., Jayapriya; T. C., Vikram Raj Mohanam; Kurien, Mary; S., Kalaiarasan; Zachariah, Ninan; T., Raghul; R. G., Arthy (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2025)
We report an uncommon case of nasal neuroglial heterotopia (NGH, glioma) presenting as midline nasal mass. Review of literature, imaging challenged and surgical management options are discussed. Unlike the more common nasal dermoid, 20% of NGH have intracranial communication which can cause post-operative life-threatening complications like CSF leak and meningitis.